SISTEM INFORMASI IDM (INDEKS DESA MEMBANGUN) BERBASIS WEB DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA (PMD) KABUPATEN SUMENEP - ach muhyiddin; Irwan Darmawan (Insand Comtech : Information Science and Computer Technology Journal, 2021)
Processing of IDM data (building village index) at the PMD service is still manual, so it still takes a lot of time and energy. This condition can increase the chances of errors in processing information and data. For this reason, it is necessary to design an information system as a substitute for amnual management, namely the IDM information system (building village index) to facilitate the work of employees in the relevant PMD service.In making this IDM application, several stages are needed in the manufacturing process, including: Data Collection, System Analysis, System Requirements, System Design, and System Development. In collecting data on the development of this IDM application, among others: the author directly visited the institution/agencies. Field studies include interviews and observations. Conducting an interview process with the agency (head of service) to obtain information about the actual situation, especially in the ongoing IDM data collection process.This research is carried out directly at the location to obtain actual information directly and can analyze the concept that will be made as a reference material for the design of an application that is needed by the institution / agency.Keywords: information system, thesis, IDM application, system design